Clopyralid Tolerance in Strawberry and Feasibility of Early Applications in Florida. Issue 4 (10th April 2018) - Sharpe, Shaun M.; Boyd, Nathan S.; Dittmar, Peter J.; MacDonald, Greg E.; Darnell, Rebecca L.
Abstract: Broadleaf species escape current integrated weed management strategies in strawberry [ Fragaria×ananassa (Weston) Duchesne ex Rozier (pro sp.) [ chiloensis×virginiana ]] production. Clopyralid is a registered POST control option, but current application timings provide suppression of only some species. Earlier clopyralid application timings may increase spray coverage to weeds at the planting hole, but strawberry plant tolerance to applications shortly after transplant is unknown. The objectives of the study were to determine the degree of clopyralid tolerance when applied to mature strawberry plants according to current management strategies, whether clopyralid absorption and translocation were involved in the tolerance response demonstrated by mature strawberry plants, and whether clopyralid could be safely applied to immature strawberry plants shortly after transplant. Clopyralid caused no damage when applied to mature strawberry plants and did not affect crop height, number of crowns, flowers, immature berries, or yield. Maximal strawberry absorption of radiolabeled clopyralid was 82% of the recovered radioactivity and reached peak (90%) absorption at 15 h. Maximal total translocation of radioactivity from the treated leaf was 17% and reached peak translocation at 52 h. Translocation was primarily to the new leaves and reproductive structures. In the early-application experiment, damage induced by clopyralid for all application timings reached 0 by 8 wk after treatment. Across all timings, maximal damage at 140 g ha −1 was 17% when applied 14 d after transplant (DATr) and 56% at 28 g ha −1 when applied at 21 DATr. Clopyralid dose did not affect the number of crowns, aboveground biomass, or yield. There was some stunting in plant height (3%) by the high labeled dose of clopyralid. Labeled dose clopyralid applications appear safe for application timings closer to strawberry transplant, though considerations of leaf cupping should be taken under consideration for label changes.